SHORT NOTICES (Heythrop journal, 2004)
Short Notices: Mary E. Mills, Images of God in the Old Testament Tod Linafelt and Timothy K. Beal, God in the Fray: A Tribute to Walter Brueggemann Kari Latvus, God, Anger and Ideology: The Anger of God in Joshua and Judges in Relation to Deuteronomy amd the Priestly Writings (Journal for the Study of the Old Testament Supplement Series 279) Edwin D. Freed, The Stories of Jesus' Birth: A Critical Introduction (The Biblical Seminar 72) David B. Capes, Old Testament Yahweh Texts in Paul's Christology (Wissenschaftliche Untersuchungen zum Neuen Testament. 2 Reihe, 47) Gerard O'Daly, Platonism Pagan and Christian: Studies in Plotinus and Augustine Alistair McFayden and Marcel Sarot, Forgiveness and Truth: Explorations in Contemporary Theology